Physical distancing in kindergarten / Nurin Syafirra Sharulfizam and Siti Fairuz Ibrahim - Sharulfizam, Nurin Syafirra; Ibrahim, Siti Fairuz (Faculty of Art and Design, 2021)
Since the beginning of the pandemic , the whole world has fallen into a sudden phase of displeasure followed by new norms that force people to wear masks and use hand sanitisers as frequently as they can. There is also social distancing practice where people have to keep their distance from other people with at least 1 meter separating them to avoid the spread of the Covid-19 virus. More people are becoming afraid of going out in public as even a slight touch of an object that has been exposed to the Covid-19 virus could possibly infect you and the community that you live in, including your family and friends. The Ministry of Health of Malaysia (MOH) has ordered a strict Standard Operating Procedure (SOP) following these events to control the vast spread of the Covid-19 virus. Infrano is a wearable device that enables users to detect whether the surrounding people have symptoms of Covid-19 infections. One of the most noticeable symptoms of Covid-19 infections is that the infected often has an increased of body temperature above normal and mostly they will catch a fever. This is one of the main points of developing this product. One of the features of Infrano is that it can scan the temperature of the user and it can also scan the temperature of the people surrounding the user within the range of 5 meters apart from the device itself.